The role of implant projection in optimizing transcatheter aortic valve implantation - Rut Álvarez-Velasco; Marcel Almendárez; Alberto Alperi; Paula Antuña; Raquel del Valle; Cesar Morís; Isaac Pascual (REC: Interventional Cardiology (English Ed.))
ABSTRACT Severe aortic stenosis is the most frequent valve condition requiring surgery, and its incidence is increasing yearly. Transcatheter aortic valve implantation (TAVI) is the first-line treatment for patients at all levels of surgical risk. Nevertheless, modifications to the procedure often appear to improve clinical outcomes. A major concern after TAVI is the higher rate of permanent pacemaker implantation (PPMI) compared with surgical valve replacement. Optimal implantation depth is crucial to reduce the burden of PPMI without causing serious complications such as valve embolization. The classic implantation technique, where the 3 cusps are aligned in the same plane, has been modified to a cusp overlap projection by isolating the noncoronary cusp and superimposing the left and right cusps. This simple modification provides optimal visualization during deployment and helps to achieve the desired implant depth to reduce conduction disturbances and PPMI. Another limitation after TAVI is coronary reaccess due to the frame of the transcatheter valve obstructing the coronary ostia. Commissural alignment of the prostheses with the native valve may facilitate selective cannulation of the coronary arteries after this procedure. This review will discuss the techniques and supporting evidence for these modifications to the deployment and implant projection methods, and how they can improve TAVI outcomes.